VALE-Emotions: Teaching mobile application for individuals with Autism Spectrum Disorders - Olmedo-Vizueta, Diana; Hernandez-Ambato, Jorge; Ávila-Pesantez, Diego; Bilotta, Eleonora; Pantano, Pietro (Enfoque UTE, 2017)
In this paper, the development of an interactive mobile application to strengthen the learning of emotion recognition in children with Autism Spectrum Disorders (ASD) is presented. This App is part of an authoring Virtual Advanced Learning Environment (VALE) devoted to support teaching and learning activities. VALE-Emotions App is based on the six basic emotions studied by (Paul Ekman, 1992), but it is not only limited to the recognition of such emotions in their highest intensity levels. In fact, the app allows for determining the effective recognition of these emotions at different intensity levels. Such intensity levels are generated by an authoring Dynamic Facial Expressions (DFE) coding using virtual avatars. Each learning activity is carried out through training and tests applications, giving to the users the opportunity of freely developing, learning, and strengthen social skills in an entertaining way. The results of the experimentation of the VALE-Emotions on subjects with ASD are also reported. In general, the participants showed efficient response at the stimulus during the developed activities obtaining a high and fast recognition of certain emotions.